An Environmentally Benign Synthesis of Octahydro-2H-chromen-4-ols via Modified Montmorillonite K10 Catalyzed Prins Cyclization Reaction - Baishya, Gakul; Sarmah, Barnali; Hazarika, Nabajyoti (Synlett, 2013)
(–)-Isopulegol undergoes Prins cyclization reaction in the presence of 20 wt% of acid-treated montmorillonite K10 to produce octahydro-2H-chromen-4-ols in good yields and with high cis selectivities under solvent-free conditions. The solid-acid catalyst can be reused without loss of its activity.
Keywords: (–)-isopulegol; Prins cyclization; H-K10 mont; octahydro-2H-chromen-4-ols; reusability